2007
DOI: 10.1016/j.jvs.2006.12.063
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of experimental arteriovenous fistula with increased matrix metalloproteinase expression in rats

Abstract: The present results confirmed our hypothesis that a high blood flow rate in the fistula vein affects the expression of MMPs and TIMP-4, resulting in the remodeling or maturation of the AVF. Remodeling is associated with degradation of collagen, with an increase in the collagen I/III ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 34 publications
4
70
0
1
Order By: Relevance
“…Immunohistochemistry showed that expression of α-SMA in the experimental group gradually increased with time. The α-SMA-positive area of the tunica intima and tunica media in the vein near the anastomotic stoma of the experimental group increased significantly compared with that in the sham operation surgery group at the same time-point in weeks 1 and 4, indicating that the expression of α-SMA may increase with increased intimal hyperplasia, consistent with previous studies (7,(29)(30)(31).…”
Section: Daysupporting
confidence: 90%
See 1 more Smart Citation
“…Immunohistochemistry showed that expression of α-SMA in the experimental group gradually increased with time. The α-SMA-positive area of the tunica intima and tunica media in the vein near the anastomotic stoma of the experimental group increased significantly compared with that in the sham operation surgery group at the same time-point in weeks 1 and 4, indicating that the expression of α-SMA may increase with increased intimal hyperplasia, consistent with previous studies (7,(29)(30)(31).…”
Section: Daysupporting
confidence: 90%
“…However, large animals have high feeding costs and a complex process of anesthesia, and it can be difficult to establish a mixed model of disease, such as with diabetes or chronic renal failure. Small animal models do not have these deficiencies (6)(7)(8)(9), and the wide use of gene knockout rats in recent years is particularly important, as it provides an important platform for the study of the mechanisms of the occurrence and development of diseases. The establishment of an arteriovenous fistula model in animals with chronic renal failure by a cuff technique has been reported (10), but the experimental results are often influenced by the technology proficiency level of the practitioner.…”
Section: Introductionmentioning
confidence: 99%
“…First, the low-resistance circuit resulting from creation of the AV anastomosis triggers an immediate increase in blood flow and wall shear stress (WSS) through the inflow artery (5)(6)(7). Second, these rapid increases in arterial blood flow and WSS stimulate an endothelium-dependent vasodilatory response in the artery and vein, mediated largely by nitric oxide (NO) and activation of matrix metalloproteinases (MMPs), that dilates both the inflow artery and outflow vein, restores WSS toward baseline, and inhibits neointimal hyperplasia development (7)(8)(9)(10)(11). Appropriate upregulation of MMPs results in matrix degradation and restructuring of the vascular scaffold, leading to luminal expansion (9,11,12).…”
Section: Vascular Remodeling and Neointimal Hyperplasia Developmentmentioning
confidence: 99%
“…Second, these rapid increases in arterial blood flow and WSS stimulate an endothelium-dependent vasodilatory response in the artery and vein, mediated largely by nitric oxide (NO) and activation of matrix metalloproteinases (MMPs), that dilates both the inflow artery and outflow vein, restores WSS toward baseline, and inhibits neointimal hyperplasia development (7)(8)(9)(10)(11). Appropriate upregulation of MMPs results in matrix degradation and restructuring of the vascular scaffold, leading to luminal expansion (9,11,12). Finally, successful vascular remodeling restores WSS toward normal levels in a vessel with increased blood flow and helps maintain luminal diameter (6,13), a key hallmark of successful outward AVF remodeling.…”
Section: Vascular Remodeling and Neointimal Hyperplasia Developmentmentioning
confidence: 99%
“…Another group of cytokines that are thought to play a key role in hemodialysis graft failure and remodeling of vein grafts used as arterial conduits are matrix metalloproteinases (MMPs) and their endogenous inhibitors, tissue inhibitors of matrix metalloproteinases (TIMPs) (6,35,36,38,49). This contention is based on the observations that an imbalance of MMP activity over TIMPs promotes the migration and proliferation of smooth muscle cells (2,21) and that certain MMPs increase the bioavailability of VEGF-A, potentially accelerating the development of intimal hyperplasia (30).…”
mentioning
confidence: 99%